2022
DOI: 10.1017/s0022149x22000153
|View full text |Cite
|
Sign up to set email alerts
|

Performance of loop-mediated isothermal amplification (LAMP) for detection of Schistosoma mansoni infection compared with Kato–Katz and real-time PCR

Abstract: The performance of loop-mediated isothermal amplification (LAMP) for detection of Schistosoma mansoni DNA from stool and urine samples in comparison with Kato–Katz and real-time polymerase chain reaction (PCR) was studied. After obtaining informed consent, 50 children participated in the present study and agreed to submit stool and urine samples. Stool samples were examined by Kato–Katz. Both real-time PCR and LAMP techniques were applied on stool and urine samples. The overall prevalence of S. mansoni was 46%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Promisingly, both LF-and RT-RPAs developed in this study were able to detect the infection in a stool sample having 1 egg/g that has previously been characterised as positive sample by KK and PCR. Several authors have also reported that urine samples can be used as the source of cfDNA of S. mansoni (Lodh et al, 2017;Fernández-Soto et al, 2019;Diab et al, 2021;Allam, 2022). In this study, urine samples were spiked with different amounts of gDNA to simulate the detection of cfDNA in clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…Promisingly, both LF-and RT-RPAs developed in this study were able to detect the infection in a stool sample having 1 egg/g that has previously been characterised as positive sample by KK and PCR. Several authors have also reported that urine samples can be used as the source of cfDNA of S. mansoni (Lodh et al, 2017;Fernández-Soto et al, 2019;Diab et al, 2021;Allam, 2022). In this study, urine samples were spiked with different amounts of gDNA to simulate the detection of cfDNA in clinical samples.…”
Section: Discussionmentioning
confidence: 99%